UTILIZATION OF FAMILY MEDICINAL PLANT DURING ANTENATAL CARE: A REVIEW - I Gusti Agung Ayu Hari Triandini (Jurnal Silva Samalas, 2019)
Family medicinal plants is an traditional medication that has been used by Indonesian people for many years. It also has been used as primary medication on family as first aid medication before medical personel handling. Family medicinal plants consist of plants that are commonly being consumed on daily life of Indonesian people especially on village. This also confirm the safety of this medication for pregnant women. Pregnant women during antenatal care have strict medication option for their illness. The could not consume antibiotic and other synthetic chemical medicine for medical treatment. The use of family medicinal plants on antenatal care could give an alternatif solution for treatment of pregnant women. Thus, this article describe beneficial of using family medicinal plant during antenatal. Since all medication should has side effect, this article also describe the limitation of family medicinal plant utilization. However, analysis of beneficial and limitation of family medicinal plants application could give strong consideration for pregnant women as their alternative medication option.